Maxims in Movie Script Percy Jackson: Sea Of Monsters - Yunita Putri, Ni Luh (Humanis; Vol 22 No 2 (2018), 2018)
This study is entitled Analysis of Maxims in Movie Script Percy Jackson: Sea of Monsters. The aims of this study are to identify the maxims applied in the movie Percy Jackson: Sea of Monsters and to identify the maxims flouted in the movie Percy Jackson: Sea of Monsters. The data of this study were obtained from the internet in the form of movie and movie script entitled Percy Jackson: Sea of Monsters. The method of collecting data was documentation method; the method was done by watching and note taking techniques. The qualitative method was used to analyze the data and the method was done by the descriptive technique. The method of presenting analysis was narrative method and was done by argumentative technique. This study found that all the types of maxims were flouted but not all the types of maxims were applied. The character of this movie mostly flouted the maxim rather than applied the maxim. The maxim that mostly flouted was the maxim of manner and the maxim that mostly applied was the maxim of quality. It can be concluded that although the characters did not apply maxim, the conversation would still be going.